ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN DALAM PEMERIKSAAN PAP SMEAR PADA WUS DI KOMUNITAS PENGAJIAN RW 12 KELURAHAN CITRODIWANGSAN LUMAJANG - sukowati, umi; Hidayati, Ainul; Fatkuriyah, Lailil (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
The main reason for the increase in cervical cancer in developing countries, including Indonesia, is the lack of effective screening programs. Cancer deaths are expected to continue to increase. The aim of this research is to determine the factors that influence delays in Pap smear examinations in women of childbearing age in the RW 12 Islamic Study Community, Citrodiwangsan Lumajang Village. This research uses a descriptive research design with a cross sectional study approach. The research population was all women of childbearing age in the RW 2 study group, Citrodiwangsan Lumajang sub-district. The sampling technique used in this research used total sampling. The inclusion criteria in this study were women of childbearing age (20-50 years), the healthy condition(not diagnosed with malignancy (cancer), present at the time of data collection, and willing to be respondents. Exclusion criteria in this study were women who were sick, respondents withdrew from the research. The research instrument was a questionnaire developed from the concept of the scope of reproductive health and guidelines for the prevention of malignant diseases in women from the Ministry of Health of the Republic of Indonesia. The results of the study showed that all respondents had good knowledge about cervical cancer and Pap smears, family support for Pap smear examinations was in the high category and all respondents had high motivation for Pap smear examinations and all respondents, however, none of the respondents underwent Pap smear screening for reasons of fear.